The measurement of particle dispersions in turbulent, four-way coupled flows - Yates, Matthew (2018)
This work contained in this thesis is the result of an industrial and academic collaboration, designed to investigate and further the present knowledge of dense turbulent dispersions. Experiments were conducted to provide support and experimental validation to a CFD code being simultaneously developed, which was able to give insight into these types of flows. Additional to this support, the aim of this thesis was to also further knowledge of key topics in this field. The experimental methodology chosen was to use a mixture of Particle Image Velocimetry and Particle Tracking Velocimetry. To discriminate between particle and liquid phases, two approaches were adopted, depending upon the experiment. In one approach, fluorescent dyes were used to tag one phase, whilst optical filters were applied to the camera lenses. In the second approach, a size-based binary mask was applied to a single image, in order to remove phase information and produce two sets of images. A number of different analysis techniques were researched and developed as part of this thesis. The performance of particle tracking algorithms was assessed to ascertain their most suitable usage. A number of different algorithms, designed to characterise particle positions, were validated against known test cases. These included the Box Counting Method, a Voronoi analysis, and Radial Distribution Functions. A further technique, known as the Particle Potential method, was also developed to characterise local clustering. Two experiments were undertaken throughout this project, both of which were developed from scratch so that full control was assured over all experimental parameters. A vertical channel experiment was designed to assess the injections of particles into a rectangular channel. These experiments allowed for an ideal test case of highly concentrated particles, without the need to achieve optical visibility through a dense solution. The experiments also provided an early test of a Refractive Index Matching candidate pair; hydrogel particles and water. The second experiment was known as the Circulating Dispersion Rig, which was designed to pump a slurry in a continuous loop in a cylindrical pipe. These experiments, due to the geometry used and dense nature of the slurry, were reliant upon trying to achieve optimum optical visibility, and so hydrogel/water mixtures were tested in advance against other, more well-utilised pairings. The experiments conducted have provided some insight into the nature of particles in turbulent flows, in particular their clustering properties. Clustering was assessed under various concentrations. Key results included analysis of these clusters using a Voronoi diagram technique, which identified four key types of cluster structure, and the parameters under which these form. Collision probabilities of particle pairs were also assessed, using Particle Tracking data and computation of relative velocities. Such information is of importance for experimental validation of CFD codes relating to dispersed two-phase flows, where particle-particle coupling must be assessed in order to provide accurate solutions. The key drive towards the future, should further experiments be desirable, would be to investigate the improvement of optically matching liquids and solids, which was felt to be the limiting factor towards achieving measurements at even higher concentrations. However, these experiments show some progress can be made in making measurements of four-way coupled turbulent flows.